S119 Inducible laryngeal obstruction masquerading as work-related asthma; a new approach. (15th November 2016) - Feary, J; Fitzgerald, B; Szram, J; Hull, J; Selby, J; Mataksori, M; Scadding, G; Cullinan, P
Abstract : Introduction: The specific inhalation challenge (SIC) is the reference standard test for diagnosis of occupational asthma in people with immunological sensitisation to a specific agent. In our occupational lung disease clinic, we recognise a separate group of patients who report symptoms consistent with inducible laryngeal obstruction (ILO) triggered by one or more agents which are generally not recognised sensitisers. Symptoms, which include throat and chest tightening, voice change, dyspnoea and wheeze, are frequently misdiagnosed as work-related asthma, "allergy" and even anaphylaxis. In such cases securing the correct diagnosis can avoid unnecessary medication use, excessive health care utilisation and occasionally loss of employment. We have designed a SIC to provide objective confirmation of the diagnosis of ILO in the occupational setting. Method: Patients are carefully selected to undergo ILO-SIC. After histamine challenge testing, spirometry and direct laryngoscopy, they are exposed, in a specialist exposure chamber, to the agent(s) which provoke their symptoms. Each challenge is bespoke according to the patient's triggers, work environment and comorbidities. Exposure is usually continued until the symptoms experienced in the workplace are reproduced, or to a level expected to cause airway irritation in a control individual. Direct laryngoscopy and measurement of spirometry is repeated and any anatomical and physiological changes noted. Results: We have carried out 30 such challenges (90% women; mean age 45 years (SD 9.4)) to date. Agents have included perfumes, household paint and hospital cleaning products. In 87% of cases, we replicated symptoms experienced in the workplace. In 53% of cases, clear changes of ILO were seen. In those with normal laryngoscopy, the SIC is equally useful in reassuring patients that symptoms experienced are not dangerous, nor consistent with anaphylaxis or similar. Following careful explanation of the diagnosis, patients are managed conservatively or referred to specialist physiotherapists or voice therapists if indicated. Asthma treatment can often be withdrawn over time. Conclusion: A precise diagnosis in cases of occupational asthma is key to successful outcome; in this setting, we increasingly see patients with occupational (or other environmental) ILO. ILO-SIC testing in specialist centres can provide objective evidence to assist diagnosis avoiding unnecessary investigation and treatment of other conditions.